Safety and efficacy of biologics, and the future direction of rheumatoid arthritis therapy. (October 2012) - Ruderman, Eric M
Eric M Ruderman is a professor of medicine at the Northwestern University Feinberg School of Medicine (IL, USA) and the clinical practice director for the division of rheumatology. His clinical interests include the medical management of rheumatoid arthritis and the spondyloarthropathies. In 2001, he established one of the first rheumatology/dermatology cooperative clinics in the USA for the management of of psoriasis and psoriatic arthritis. He has been an investigator in over 50 clinical trials studying both biologic and nonbiologic therapies for rheumatic diseases. In line with his ongoing interest in patient safety, he has served on the data safety monitoring boards for a number of NIH and industry-sponsored clinical trials, and he currently serves as vice-chair for Northwestern University's Institutional Review Board.